Delayed Enhancement of Intracranial Atherosclerotic Plaque Can Better Differentiate Culprit Lesions: A Multiphase Contrast-Enhanced Vessel Wall MRI Study - Sun, Beibei; Wang, Lingling; Li, Xiao; Zhang, Jin; Zhang, Jianjian; Tian, Jiaqi; Mossa-Basha, Mahmud; Xu, Jianrong; Zhou, Yan; Zhao, Huilin; Zhu, Chengcheng (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Intracranial plaque enhancement (IPE) identified by contrast-enhanced vessel wall MR imaging (VW-MR imaging) is an emerging marker of plaque instability related to stroke risk, but there was no standardized timing for postcontrast acquisition. We aim to explore the optimal postcontrast timing by using multiphase contrast-enhanced VW-MR imaging and to test its performance in differentiating culprit and nonculprit lesions.MATERIALS AND METHODS: Patients with acute ischemic stroke due to intracranial plaque were prospectively recruited to undergo VW-MR imaging with 1 precontrast phase and 4 consecutive postcontrast phases (9 minutes and 13 seconds for each phase). The signal intensity (SI) values of the CSF and intracranial plaque were measured on 1 precontrast and 4 postcontrast phases to determine the intracranial plaque enhancement index (PEI). The dynamic changes of the PEI were compared between culprit and nonculprit plaques on the postcontrast acquisitions.RESULTS: Thirty patients with acute stroke (aged 59 ± 10 years, 18 [60%] men) with 113 intracranial plaques were included. The average PEI of all intracranial plaques significantly increased (up to 14%) over the 4 phases. There was significantly increased PEI over the 4 phases for culprit plaques (an average increase of 23%), but this was not observed for nonculprit plaques. For differentiating culprit and nonculprit plaques, we observed that the performance of IPE in the second postcontrast phase (cutoff = 0.83, AUC = 0.829 [0.746–0.893]) exhibited superior accuracy when compared with PEI in the first postcontrast phase (cutoff = 0.48; AUC = 0.768 [0.680–0.843]) (P = .022).CONCLUSIONS: A 9-minute delay of postcontrast acquisition can maximize plaque enhancement and better differentiate between culprit and nonculprit plaques. In addition, culprit and nonculprit plaques have different enhancement temporal patterns, which should be evaluated in future studies.AUCarea under the curveICCintraclass correlation coefficientICADintracranial atherosclerosis diseaseIPEintracranial plaque enhancementPEIplaque enhancement indexPIpituitary infundibulumROCreceiver operating characteristicSDstandard deviationVWvessel wall